Identification of Settlements in Disaster-Prone Areas and Disaster Mitigation Strategies in Denpasar City - Wijaya Putra, Anak Agung Gde Sutrisna; Indrayani, Indrayani (International Journal of Social Service and Research, 2026)
Denpasar City, as the economic and administrative center of Bali Province, faces significant disaster risks due to its geographical location and rapid urbanization. This study aims to identify and map residential areas located in disaster-prone zones in Denpasar and to formulate appropriate disaster mitigation strategies. A spatial analysis approach was employed, utilizing Geographic Information System (GIS) technology to overlay settlement distribution maps with multi-hazard disaster-prone maps (tsunami, earthquake, liquefaction, and flood) obtained from the Denpasar City Rencana Tata Ruang Wilayah (RTRW) and related agency data. The analysis was complemented by field surveys to verify the conditions of affected settlements. The results reveal that a substantial portion of residential areas in Denpasar is situated within high-risk zones. Specifically, settlements in South Denpasar District are highly exposed to tsunami, earthquake, and liquefaction threats, while flood risks are more widespread across West, South, East, and North Denpasar. The findings underscore a critical gap between rapid spatial development and disaster risk considerations. Consequently, this study recommends the integration of disaster risk zoning into spatial planning, the development of disaster-resistant infrastructure, the strengthening of building codes, and the establishment of clear relocation protocols for settlements in the highest-risk areas. The study implies an urgent need for coordinated efforts between the government and communities to enhance urban resilience and minimize potential future losses.